Borderline personality traits and disorder: predicting prospective patient functioning - Hopwood, Christopher J. (2010)
OBJECTIVE: Decisions about the composition of personality assessment in DSM-V will be heavily influenced by the clinical utility of candidate constructs. This study addressed one aspect of clinical utility by testing the incremental validity of five-factor model personality traits and Borderline Personality Disorder (BPD) symptoms for predicting prospective patient functioning. METHOD: Five-factor personality traits and BPD features were correlated with one another and predicted 2, 4, 6, 8, and 10-year psychosocial functioning scores for 362 personality-disordered patients. RESULTS: Traits and symptom domains related significantly and pervasively to one another and to prospective functioning. FFM extraversion and agreeableness tended to be most incrementally predictive of psychosocial functioning across all intervals; cognitive and impulse action features of BPD features incremented FFM traits in some models. CONCLUSIONS: These data suggest that BPD symptoms and personality traits are important long-term indicators of clinical functioning that both overlap with and increment one another in clinical predictions. Results support the integration of personality traits and disorders in DSM-V.